Ecological correlates of polyphenism and gregarious roosting in the grass yellow butterfly Eurema elathea (Pieridae) - Ruszczyk,A. (2004)
Eurema elathea adults were censused weekly (1992-1994) in six night-roosts around a forest fragment on a farm, and in two roosts in the urban area of Uberlândia, Minas Gerais, Brazil. Males were grouped in six phenotypic classes. These were based on a range between having a conspicuous wide black bar at the dorsal forewing inner margin (wet season dark morphs) and the absence of that bar (dry season light morphs). The body mass and wing area of co-occurring morphs were compared: differents morphs showed similar means. The abundance of butterflies and morph frequencies varied in close relation to humidity (rainfall). Individuals were infrequent and monomorphically dark in the wet season while light morphs predominated in dry periods when population peaked. A lower fraction of recaptured individuals and higher recruitment were recorded compared to other night-roosting butterflies. Dispersal potential was similar between the sexes and varied seasonally with a more sedentary population in dry periods. The maximum residence time recorded was 91 days for a female and 84 days for a male. The fraction of individuals that moved from one roosting site to another was similar in both sexes and male morphs, but significantly higher on the farm than in the urban area. Also, a significantly higher fraction (21.3%) of marked butterflies was recaptured in the urban area than on the farm (15.6%), suggesting a behavioral modification for sedentariness in the urban individuals. The selective forces shaping a gregarious roosting habit in E. elathea and other butterflies are discussed and a protocooperational strategy for saving energy is proposed.